1991
DOI: 10.1111/j.1365-2672.1991.tb04434.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of siderophores in the biocontrol of Pseudomonas tolaasii by fluorescent pseudomonad antagonists

Abstract: A number of pseudomonad bacteria were investigated for their in vitro antagonism on agar against Pseudomonas tolaasii, the causative agent of bacterial blotch of the cultivated mushroom. Addition of FeCl3 to the culture medium suppressed the antagonism in 14 of the 20 bacteria tested and the production of a substance with an absorption peak at 400 nm by all antagonists was eliminated by the presence of Fe3+. Both observations indicated that siderophores could be involved in the mode of action of some antagonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…is siderophore-mediated competition for iron In our experience (Guillot andLeclerc 1993), 40% were (Freedman et al 1989 ;Henry et al 1991). An inhibitory effect Pseudomonas species with about 90% of strains producing a against pathogenic and spoilage bacteria by Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 77%
“…is siderophore-mediated competition for iron In our experience (Guillot andLeclerc 1993), 40% were (Freedman et al 1989 ;Henry et al 1991). An inhibitory effect Pseudomonas species with about 90% of strains producing a against pathogenic and spoilage bacteria by Pseudomonas spp.…”
Section: Introductionmentioning
confidence: 77%
“…(1996) showed that a Pseudomonas strain from the sediments of wells, which inhibited several enteropathogenic bacteria on agar, could also cause inhibition in an aquatic environment. Similarly, antagonism by a number of Pseudomonas bacteria against Pseudomonas tolaasii , shown in vitro on agar, could be reproduced under commercial mushroom growing conditions (Henry et al . 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, Pybus el al. (1994) found that addition of iron eliminated the inhibitory activity of Vibrio anguillarum against Vibrio ordalii, and several studies (Kloepper et al 1980;Freedman et al 1989;Henry et al 1991) have shown that addition of iron to media decreases the inhibitory effect of pseudomonads in agar plate assays. Part of the inhibitory activity of Pseudomonas observed in the present study is attributed to their siderophore formation or to antibacterial compounds under iron regulation.…”
Section: Discussionmentioning
confidence: 99%